Non-destructive CT Method for Spatially Resolved Measurement of Elemental Content and Density of Li-B Alloys - Huang, Haifeng; Wu, Chen; Liu, Zhijian; Zeng, Xiaopeng; Chen, Libao (Frontiers in Chemistry, 2020)
Lithium-boron (Li-B) alloys play an important role in the fields of thermal batteries and Li metal batteries, where the electrochemical performance is highly dependent on microstructure homogeneity and the Li content. In this study, computed tomography (CT) scanning has been firstly used to study the elemental content and spatial distribution of Li in a Li-B alloy. For a commercial Li-B alloy, quantitative relationships between the CT values, [Hu], and the weight percent of Li, wT−Li, and the density, ρLi−B, that is, [Hu] =13563.836.2×wT-Li-2.8-1,016.2 and [Hu] = 790.1 × ρLi−B − 1, 016.2, respectively. The experimental data were found to be in good agreement with current theory. The CT scanning method was non-destructive, and proved to be fast, highly accurate, and low-cost for the characterization of Li-B alloy ingots in terms of elemental composition, density, and uniformity.